Dietary pattern and practices during pregnancy and in puerperium a rural study - Bhardwaj, N; Yunus, M; Hasan, S Badrul; Zaheer, M (Indian Journal of Community Health, 1994)
An longitudinal study was carried out for a period of one year from May 1987 to April 1988. 212 pregnant women were registered, in the Jaxuan block of district Aligarh in Western Uttar Pradesh for studying their dietary pattern 81 dietary practices in pregnancy and inpuerperim respectively. There was no significant change in diet during pregnancy but during puerperium there was increase in food consumption as a traditional practice. The mean caloric consumption in various social classes showed a consistent rise with increase in socio-economic status and ranged from 1850 calories in social class V to 2375 calories in social class I. Since 68.6% of women belong to social class IV8iV, the single most important determinent for inadequate calorie intake was poverty. Out of208 babies born, 52 babies could only be weighed Si they were all low birth weight babies with an average weight of2.1 kg.